2018
DOI: 10.3390/molecules23030650
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a HPLC-UV Method for Extraction Optimization and Biological Evaluation of Hot-Water and Ethanolic Extracts of Dendropanax morbifera Leaves

Abstract: Dendropanax morbifera Leveille (Araliaceae) has been used in traditional oriental remedies for cancer, inflammation, diabetes, and thrombosis. However, a validated analytical method, standardization, and optimization of extraction conditions with respect to biological activity have not been reported. In this study, a simple and validated HPLC method for identifying and quantifying active substances in D. morbifera was developed. Hot water and ethanolic D. morbifera leaf extracts from different production regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Similarly, Choi et al studied the effect of reducing power on the antioxidant activity of DMLE and showed that an increase in reducing power with an increasing concentration of ethanol as the extraction solvent led to the highest reducing power at 80% ethanol extract, but a decreasing trend at 100% ethanol. This was attributed to the difference in the content of phenolic compounds in DMLE [28]. Another study on the correlation between TF content and the antioxidant potential of DMLE in each ethanol concentration reported that although TF content increased with increasing ethanol concentration and reached the highest level at 80% ethanol extract, it decreased at 100% ethanol.…”
Section: Determination and Validation Of The Optimal Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Choi et al studied the effect of reducing power on the antioxidant activity of DMLE and showed that an increase in reducing power with an increasing concentration of ethanol as the extraction solvent led to the highest reducing power at 80% ethanol extract, but a decreasing trend at 100% ethanol. This was attributed to the difference in the content of phenolic compounds in DMLE [28]. Another study on the correlation between TF content and the antioxidant potential of DMLE in each ethanol concentration reported that although TF content increased with increasing ethanol concentration and reached the highest level at 80% ethanol extract, it decreased at 100% ethanol.…”
Section: Determination and Validation Of The Optimal Conditionsmentioning
confidence: 99%
“…These findings were consistent with those of a study on the preventive effects of DMLE on gout, whereby the main components of the ethanol extract, whose powerful antioxidant function led to the anti-gout activity, were chlorogenic acid and rutin [37]. In another study on chlorogenic acid and rutin contents in D. morbifera leaves according to their different places of origin and extraction solvents, although the contents varied according to the place of origin, chlorogenic acid and rutin were still found to be the main components of DMLE, and the 80% ethanol extract condition exhibited the highest extract contents with the most outstanding antioxidant activity [28].…”
Section: Chemical Composition Analysis In Dmlementioning
confidence: 99%
“…longa was performed using an Alliance 2695 HPLC system (Waters, Milford, MA, USA) equipped with a photodiode array detector 44 . An Agilent Zorbax extended C18 analytical column (5 µm, 150 mm × 5 mm) was used with a mobile phase consisting of a mixture of solvent A (acetonitrile) and B (water containing 0.2% phosphoric acid, pH 3.5).…”
Section: Instrumentation and Chromatographic Conditions For C Longa mentioning
confidence: 99%
“…Dendropanax morbifera (Aralicaceae), called ginseng tree, is a perennial tree that grows in forests in the southern regions in South Korea. The leaf, stem, and root of D. morbifera have been used in traditional medicine to treat infectious diseases, dermatopathy, dysmenorrhea and migraine [1,2]. To date, a few studies have been carried out investigating D. morbifera as a functional food and medicinal source [2].…”
Section: Introductionmentioning
confidence: 99%